Diphenyl diselenide abrogates brain oxidative injury and neurobehavioural deficits associated with pesticide chlorpyrifos exposure in rats (2018)
Exposure to pesticide chlorpyrifos (CPF) is associated with neurodevelopmental toxicity both in humans and animals. Diphenyl diselenide (DPDS) is a simple synthetic organoselenium well reported to possess antioxidant, anti-inflammatory and neuroprotective effects. However, there is paucity of information on the beneficial effects of DPDS on CPF-mediated brain injury and neurobehavioural deficits. The present study investigated the neuroprotective mechanism of DPDSin rats sub-chronically treated with CPF alone at 5 mg/kg body weight or orally co-treated with DPDS at 2.5 and 5 mg/kg body weight for 35 consecutive days. Endpoint analyses using video- tracking software in a novel environment revealed that co-treatment with DPDS significantly (p < 0.05) pro- tected against CPF-mediated locomotor and motor deficits precisely the decrease in maximum speed, total distance travelled, body rotation, absolute turn angle, forelimb grip strength as well as the increase in negative geotaxis and incidence of fecal pellets. The enhancement in the neurobehavioral activities of rats co-treated with DPDS was verified by track plot analyses. Besides, DPDS assuaged CPF-induced decrease in acetylcholinesterase and antioxidant enzymes activities and the increase in myeloperoxidase activity and lipid peroxidation level in the mid-brain, cerebral cortex and cerebellum of the rats. Histologically, DPDS co-treatment abrogated CPF- mediated neuronal degeneration in the cerebral cortex, dentate gyrus and cornu ammonis3 in the treated rats. In conclusion, the neuroprotective mechanisms of DPDS is related to the prevention of oxidative stress, enhance- ment of redox status and acetylcholinesterase activity in brain regions of the rats. DPDS may be a promising chemotherapeutic agent against brain injury resulting from CPF exposure.